Social influence and 10-year cardiovascular risk impact of tobacco use among adults in Pyin Oo Lwin, Myanmar - Zar, Khin Thu; Yuasa, Motoyuki (International Journal Of Community Medicine And Public Health, 2025)
Background: Tobacco use is more common in developing countries than in developed countries. This study aimed to identify the patterns of tobacco use and determine the relationships between social factors, the level of social influence, Framingham 10-year cardiovascular disease risk, and current tobacco use among adults in Pyin Oo Lwin, Myanmar. Methods: This was a community-based, cross-sectional study, and it included 430 adults, 18 years of age and above, who resided in Pyin Oo Lwin township and were willing to participate. Results: This study revealed that the prevalence of tobacco use among adults in Pyin Oo Lwin was 59.5%. Most respondents were men (70.5 %), and almost a third of current tobacco users (28.9 %) used only smokeless tobacco. The Framingham 10-year cardiovascular disease risk was highly associated with current tobacco use (p<0.001). The participants with a high level of social influence were 9.5 times more likely to be tobacco users compared to the participants with a low level of social influence. The results showed social influence levels and peer influence, such as friends using tobacco products and friends offering tobacco products, were significant factors in current tobacco use (p<0.050). Conclusions: Tobacco taxes should be increased to minimize tobacco use among Myanmar adults. Early prevention programs for cardiovascular disease risk and healthy lifestyle behavior change promotion programs should be established for Myanmar's adults.